2015
DOI: 10.1080/10509674.2015.1043481
|View full text |Cite
|
Sign up to set email alerts
|

Bible College Participation and Prison Misconduct: A Preliminary Analysis

Abstract: We analyzed whether a Bible college program had an impact on prison misconduct by examining 230 offenders in the Texas prison system. Findings suggest participation in the Bible college significantly improved offender behavior, reducing misconduct by one discipline conviction per participant. The results also showed that participation significantly decreased the risk of incurring a discipline conviction, lowering it by 65 percent for minor misconduct, 80 percent for major misconduct, and 68 percent for any mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
(21 reference statements)
0
24
0
1
Order By: Relevance
“…Issues surrounding inmate social factors were resolved with the help of spiritual-life enhancement (Duwe, et, al., 2015), and it was discovered that simple "program-participation" became a means by which inmates experienced fewer conduct problems (Lahm, 2009;Hackman, 1997). And, time-management conflicts gave rise to a solution wherein a reprioritization of inmate activities was found to be beneficial (Esperian, 2010;McCarthy, 2006;Batchelder & Pippert, 2001) Carver and Harrison's (2016) research, along with Ray, Grommon, and Rydberg (2016), demonstrated that when goals are misaligned, reducing the stigma associated with prison was the first step in aligning those goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues surrounding inmate social factors were resolved with the help of spiritual-life enhancement (Duwe, et, al., 2015), and it was discovered that simple "program-participation" became a means by which inmates experienced fewer conduct problems (Lahm, 2009;Hackman, 1997). And, time-management conflicts gave rise to a solution wherein a reprioritization of inmate activities was found to be beneficial (Esperian, 2010;McCarthy, 2006;Batchelder & Pippert, 2001) Carver and Harrison's (2016) research, along with Ray, Grommon, and Rydberg (2016), demonstrated that when goals are misaligned, reducing the stigma associated with prison was the first step in aligning those goals.…”
Section: Discussionmentioning
confidence: 99%
“…One solution, albeit controversial, is suggested by Duwe, Hallett, Hays, Jang, & Johnson, (2015), in the form of a religious intervention. These authors reported that enrollment in a "bible college" program produced particularly impressive results.…”
Section: Inmate Social Factorsmentioning
confidence: 99%
“…We suggest further investigation of other mental health disorders as possible mediators of R/S and violence, such as antisocial and borderline personality disorders, which can be associated with more aggressive behaviors [46]. Furthermore, interventional methodological designs to reduce aggressive and criminal behavior have been showing satisfactory results [43,47] and should be considered when exploring possible mechanisms of action of the R/S dimension.…”
Section: Plos Onementioning
confidence: 95%
“…In a study of incarcerated individuals who participated in an arts program in England, Hughes (2005) reported that participants improved their discipline records by 29% compared with reports prior to participation. Using propensity score matching, Duwe et al. (2015) observed that participation in a postsecondary religion course in prison significantly reduced the risk of misconduct compared with matched nonparticipants.…”
Section: Theoretical Framework and Propositionsmentioning
confidence: 99%